Development of a Calculation Methodology for the Ventilation on a Besis of a Mobile Unit; Journal of Physics: Conference Series; Vol. 671 : Innovations in Non-Destructive Testing (SibTest 2015) - Sechin A. A. Andrey Alexandrovich (2016, 2016)
Title screen